Kemelayuan dan Diaspora Bugis di Papua: Merentas antara Ruang dan Bahasa - Sukardi Gau (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Malay and Asia influenca was entered in Papua started from Papua people have relation with the comer from other place in Nusantara at 7th century, but no explaination can tell about when, where, and how the Buginese to move to Papua, except the information about the migration and distribution of Buginese to Papua after Irian Jaya returned to Indonesian Republic.According to that, on this paper, the terminology of Buginese diaspora can supposed be approriate for understanding his history of Buginese migration from their village in South Sulawesi to the eastern zone of Malay is Papua.So the goal of this paper is to discuss about develop, distribution, profile, dynamic of Buginese in Papua, and the other Malay issues, included their language using.